2009
DOI: 10.2164/jandrol.108.007005
|View full text |Cite
|
Sign up to set email alerts
|

Fifty‐ two—Week Treatment With Diet and Exercise Plus Transdermal Testosterone Reverses the Metabolic Syndrome and Improves Glycemic Control in Men With Newly Diagnosed Type 2 Diabetes and Subnormal Plasma Testosterone

Abstract: Men with the metabolic syndrome (MetS) and type 2 diabetes (T2D) often have low testosterone levels. Elevating low testosterone levels may improve features of the MetS and glycemic control. In a single blind, 52-week randomized clinical trial, the effects of supervised diet and exercise (D&E) with or without transdermal testosterone administration on components of the MetS in hypogonadal men with the MetS and newly diagnosed T2D were assessed. A total of 32 hypogonadal men (total testosterone ,12.0 nmol/L) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
269
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(298 citation statements)
references
References 26 publications
12
269
1
12
Order By: Relevance
“…In these men, there is an increase of serum cholesterol, LDL-cholesterol and triglycerides and a decrease in HDL-cholesterol (20). The role of testosterone is further corroborated by the favorable effects of administration of testosterone on lipid profiles in a study of men with newly diagnosed diabetes mellitus and the metabolic syndrome (13 There is evidence from epidemiological studies on metabolic syndrome that there is an inverse relationship between circulating levels of testosterone and blood pressure. Lower levels of testosterone in men are associated with higher blood pressure, left ventricular mass, and left ventricular hypertrophy for review (22).…”
Section: Testosterone and Lipidsmentioning
confidence: 94%
See 2 more Smart Citations
“…In these men, there is an increase of serum cholesterol, LDL-cholesterol and triglycerides and a decrease in HDL-cholesterol (20). The role of testosterone is further corroborated by the favorable effects of administration of testosterone on lipid profiles in a study of men with newly diagnosed diabetes mellitus and the metabolic syndrome (13 There is evidence from epidemiological studies on metabolic syndrome that there is an inverse relationship between circulating levels of testosterone and blood pressure. Lower levels of testosterone in men are associated with higher blood pressure, left ventricular mass, and left ventricular hypertrophy for review (22).…”
Section: Testosterone and Lipidsmentioning
confidence: 94%
“…The maximum effect was attained after nine months of testosterone administration. A single-blind randomized study of testosterone administration to men with metabolic syndrome and recent onset of diabetes mellitus established also beneficial effects of testosterone on blood pressure over and above the effects of diet and exercise (13). These effects are persistent as demonstrated in a study of men receiving testosterone treatment up to 9.5 years (21).…”
Section: Testosterone and Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In view of the association between hypogonadism and diabetes, researchers have postulated whether TRT can also improve metabolic parameters in diabetes. Studies have shown an association between TRT and reductions in HbA1c, 32 improvement in insulin resistance 33 and a reduction in body mass index. 34 A large Australian study (T4DM) is currently underway to assess whether …”
Section: Hypogonadism In Type 2 Diabetesmentioning
confidence: 99%
“…There is a positive correlation between serum testosterone levels and insulin sensitivity in men across the full spectrum of glucose tolerance [41] and an improvement of insulin sensitivity was noted after testosterone replacement. The effects of testosterone administration on glycemic control of men with diabetes mellitus were until recently much less certain [42] but there are recent reports indicating a favorable effect of testosterone in addition to diet and exercise [43]. By increasing LBM and reducing fat mass, testosterone therapy modulates insulin resistance and risk of metabolic syndrome [42].…”
Section: Improving Metabolic Syndrome and Diabetes Type 2 Cardiovascmentioning
confidence: 99%